The NF‐κB regulator Bcl‐3 modulates inflammation during contact hypersensitivity reactions in radioresistant cells. Issue 4 (12th February 2015) - Tassi, Ilaria; Rikhi, Nimisha; Claudio, Estefania; Wang, Hongshan; Tang, Wanhu; Ha, Hye‐lin; Saret, Sun; Kaplan, Daniel H.; Siebenlist, Ulrich
<x xml:space="preserve">Abstract</x> Bcl‐3 is an atypical member of the IκB family. Bcl‐3 functions as a cofactor of p50/NF‐κB1 or p52/NF‐κB2 homodimers in nuclei, where it modulates NF‐κB‐regulated transcription in a context‐dependent way. Bcl‐3 has tumorigenic potential, is critical in host defense of pathogens, and has been reported to ameliorate or exacerbate inflammation, depending on disease model. However, cell‐specific functions of Bcl‐3 remain largely unknown. Here, we explored the role of Bcl‐3 in a contact hypersensitivity (CHS) mouse model, which depends on the interplay between keratinocytes and immune cells. Bcl‐3‐deficient mice exhibited an exacerbated and prolonged CHS response to oxazolone. Increased inflammation correlated with higher production of chemokines CXCL2, CXCL9, and CXCL10, and consequently increased recruitment of neutrophils and CD8+ T cells. BM chimera experiments indicated that the ability of Bcl‐3 to reduce the CHS response depended on Bcl‐3 activity in radioresistant cells. Specific ablation of Bcl‐3 in keratinocytes resulted in increased production of CXCL9 and CXCL10 and sustained recruitment of specifically CD8+ T cells. These findings identify Bcl‐3 as a critical player during the later stage of the CHS reaction to limit inflammation via actions in radioresistant cells, including keratinocytes.